RESPONSIBILITY TO PROTECT: A NEW FORM OF HUMANITARIAN INTERVENTION? - Irawati Handayani (Padjadjaran Journal of International Law, 2017)
AbstractHuman rights issues have become a common topic that continuously being discussed around the world. The major concern of international community on the protection of basic human rights leads to a challenge for the nation state to fulfill its commitment to protect the basic rights of their people from the possibility of harm that comes from internally or externally. Meanwhile, the principle of mutual understanding and respect among states and non-interference to domestic affairs of particular state has been generally recognized as the main principle in international law. Sometimes, a conflict that occurred inside a state, which is theoretically becomes a domestic issue, could be escalated and become a mutual concern of international society. When a human right violation occurred inside a state, ideally international community can not only ‘sit and watch’. Especially when the violations are classified as grave breaches of human rights. The world community has a moral obligation to offer an assistance and search a solution to end that violations.It is cleary noted that Article 2 (4) and Article 2 (7) United Nations (UN) Charter should not be regarded as an absolute prohibition of interference. Those articles are the limitation so that the intervention should not endangered territorial integrity, political independence and not contrary to the purposes of UN. However, the territorial integrity would be broken if the state lose their territory permanently, and in the context of humanitarian intervention there is no taking over a territory, since the main purpose is only to restore the condition as a result of human rights violation that occurred. Based on this assumption so intervention not contrary to UN Charter. One thing should be emphasized is that the requirements for intervention have to be very clear.Following an unsettled debate on criterion of humanitarian intervention, a few years ago there were a new concept which is believed as an improvement or a ‘new face’ from humanitarian intervention. It called the doctrine of Responsibility to Protect. Generally, both of these concepts have similarity, especially with the main purpose on guarantee basic human rights and provide such protection when the authorized government is unable and unwilling to do so. However, the RtoP doctrine can not also avoid its controversy. The main discussion on this doctrine particularly questioning the legal status of this doctrine in international law and whether RtoP is only a new form of humanitarian intervention.Keywords: humanitarian internvention, responsibility to Protect (R2P), duty to protect, non intervention, customary international law.AbstrakIsu mengenai HAM telah menjadi topik umum yang terus menerus didiskusikan diseluruh dunia. Perhatian utama dari komunitas internasional dalam hal perlindungan mendasar HAM selanjutnya menantang negara-negara untuk melakukan pemenuhan komitmen mereka agar melakukan perlindungan hak-hak mendasar dan tindakan yang dapat mengancam baik secara internal maupun secara eksternal. Sementara itu prinsip salaing pengertian dan penghargaan antar negara, prinsip non-intervensi dalam hubungan domestik telah diakui sebagai prinsip utama dalam hukum internasional. Kadang, konflik yang lahir di dalam negeri, yang secara teori adalah konflik domestik, dapat menjadi perhatian bersama masyarakat internasional. Pada saat terjadi pelanggaran HAM didalam suatu negara, seharusnya komunitas internasional tidak hanya ‘duduk dan melihat’. Khususnya pada saat terjadi pelanggaran yang dikategorikan sebagai pelanggaran berat terhadap HAM. Komunitas negara mempunyai kewajiban moral untuk menawarkan bantuan dan mencari solusi untuk mengakhiri pelanggaran tersebut.Seperti yang dijelaskan dalam Pasal 2 (4) dan Pasal 2 (7) Piagam PBB, pasal-pasal ini tidak dapat diangap sebagai larangan absolut interfensi. Pasal-pasal tersebut adalah pembatasan sehingga intervensi tidak membahayakan inegritas wilayah, indpendensi politik dan tidak bertentangan dengan tuujuan PBB. Meskipun demikian, integritas wilayah dapat hilang apabila negara kehilangan wilayahnya secara permanen, dan dalam konteks intervensi kemanusiaan tidak ada pengambil alihan wilayah, karena tujuan utamanya hanya untuk mengembalikan kedaaan pada saat terjadinya pelanggaran HAM. Berdasarkan asumsi tersebut, maka intervensi tidak bertentangan dengan Piagam PBB. Hal lain yang harus diperjelas bahwa alasan intervensi haruslah jelas.Mengikuti perdebatan yang tidak kunjung sellesai tentang kriteria intervensi kemanusiaan, beberapa tahun yang lalu dibuatlah suatu konsep yang dianggap sebagai wajah baru dari intervensi kemanusiaan. Secara umum, kedua konsep ini mempunyai kesamaan, terutama dengan tujuan utama dalam menjamin HAM dan menyediakan sejumlah perlindungan pada saat pemerintah yang berwenang tidak mampu dan tidak dapat memberikan jaminan HAM. Meskipun demikian, Doktin RtoP tidak dapat terhindar dari kontroversi. Diskusi utama dari doktrin ini adalah pertanyaan tentang status hukum dari doktrin hukum internasional dan apakah RtoP merupakan bentuk lain dari intervensi kemanusiaaan. Kata kunci: intervensi kemanusiaan, tanggung jawab untuk melindungi (R2P), kewajiban perlindungan, non intervensi ̧ hukum kebiasaan internasional.